The Effect of Emotional Intelligence on the Level of Understanding of Accounting - Aswar Rahmat (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2022)
The purpose of this study was to examine the influence of emotional intelligence on the level of understanding of accounting in Accounting students at the University of West Sulawesi. The type of data used is quantitative data and the data source in this study is primary data. The research data was obtained from a questionnaire filled out by students of the Accounting Study Program at the University of West Sulawesi. The population in this study were 406 students of Accounting Study Program, University of West Sulawesi, class of 2016-2018. The sampling technique used a purposive sampling method with 81 respondents. The results of the analysis show that emotional intelligence has a significant effect on the level of understanding of accounting.